Gametophyte morphogenesis of a fern Polystichum aculeatum L. Roth of Ukraine's flora in culture in vitro - Babenko, L.M.; Romanenko, K.O.; Shcherbatiuk, M.M.; Vasheka, O.V.; Romanenko, P.O.; Negretsky, V.A.; Kosakivska, I.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
The spore morphology and the germination pattern, as well as peculiarities of the gametophyte development of a wild fern Polystichum aculeatum (L.) Roth. in culture in vitro are studied. The spore germination is found to be dependent on the duration of their storage. 80—95 % of freshly-picked spores have germinated in culture in vitro. After the 4—6-month storage under lab conditions, the germinating ability ranged within 68—95 %; after 1.5 months, it did not exceed 20 %. The time limits of four stages in gametophyte morphogenesis are singled out and established. The spore germination and the protonema formation in P. Aculeatum are shown to occur according to the Vittaria-pattern, prothallium development — according to the Aspidium-pattern.